THE ROLE OF INTERACTIVE METHODS IN THE DEVELOPMENT OF STUDENT’S CRITICAL THINKING (Web of Teachers: Inderscience Research, 2023)
Critical thinking is based on the ability to express one's opinion on a given issue or problem, to critically re-perceive the opinions of others, to justify and maintain one's point of view.